Social motives in network formation: an experiment - van Dolder, Dennie; Buskens, Vincent (2009)
Literature on network formation typically assumes that people create and remove relations as to maximize their outcome in the network. It is mostly neglected that people might also care about the outcomes of others when creating and removing links. In the current paper, we develop an experiment to investigate whether people show preferences that involve the outcomes of others during network formation. We find varying evidence for effects of social motives in the settings we compare in the experiment. In the final part of the paper, we discuss some explanations for these findings.